CONSTRUCTION OF INTERGRATED SCIENCE LEARNING MATERIAL INTEGRATED TYPE TO DEVELOP STUDENTS SCIENTIFIC LITERACY - Syam, Sri Rahmadani; Hernani, Hernani; Solihat, Rini (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Science learning in curriculum 2013 emphasizes to integrated learning approach that can improve the efficiency and effectiveness of learning and achievement of basic competencies. In addition, scientific literacy of junior high school students in Indonesian is low. Based on this, it is necessary to construction of integrated science learning materials. integrated science learning materials can be compiled by integrated type. The purpose of this research is to describe construction, determine the feasibility and effectiveness learning material. The research method used is Research and Development (R&D). Construction of learning materials refers to the 4-D development model that reduced into 3-D. Feasibility test using questionnaire whereas effectiveness of learning materials using objective test and questionnaire. The results showed that learning material is very feasible to used in limited test on average percentage of each aspect >76% whereas effectiveness of learning material showed that learning material can improve scientific literacy of student on probability value is (p) Sig = 0,000<a = 0.05 and average percentage of teacher and student response is 79.24 % and 80.90% with very good category. Thus, it is concluded that learning material very feasible to use in developing scientific literacy of student in the school.